2011
DOI: 10.1021/la201064d
|View full text |Cite
|
Sign up to set email alerts
|

Using Microcontact Printing of Fibrinogen to Control Surface-Induced Platelet Adhesion and Activation

Abstract: The ability to promote or inhibit specific platelet–surface interactions in well-controlled environments is crucial to studying fundamental adhesion and activation mechanisms. Here, microcontact printing was used to immobilize human fibrinogen covalently in the form of randomly placed, micrometer-sized islands at an overall surface coverage of 20, 50, or 85%. The nonprinted background region was blocked with covalently immobilized human albumin. Platelet adhesion and morphology on each substrate were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 49 publications
2
47
1
Order By: Relevance
“…[20][21][22][23] In this work, we apply microcontact printing to create micro/nanoscale patterns of matrix proteins that mediate platelet adhesion and activation, to demonstrate that the microenvironmental geometry directly mediates platelet physiology and function. Specifically, we demonstrate that platelet a-granule secretion is spatially regulated at the micro/nanoscale via rearrangement of the actin cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] In this work, we apply microcontact printing to create micro/nanoscale patterns of matrix proteins that mediate platelet adhesion and activation, to demonstrate that the microenvironmental geometry directly mediates platelet physiology and function. Specifically, we demonstrate that platelet a-granule secretion is spatially regulated at the micro/nanoscale via rearrangement of the actin cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…A second patch of an immobilized proadhesive protein downstream of the agonist is used to capture primed platelets. In the present study, fibrinogen was used as the protein in the capture region as it has been previously demonstrated to effectively arrest primed platelets; 2,11 however, other capture proteins (e.g., collagen or vWF) could easily be incorporated. This assay would not have the required sensitivity without the phenomenon of platelet margination toward flow chamber walls in laminar flow of whole blood.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that a platelet population allowed to transiently interact with a stimulating surface patch has an increased propensity to activate and adhere downstream. 2,11 This phenomenon is largely a) Author to whom correspondence should be addressed; present address: 20 S 2030 E., Rm. 108A, Salt Lake City, Utah 84112; electronic mail: vladimir.hlady@utah.edu due to the margination of platelets in flowing blood which was utilized here to create a new type of antiplatelet agent assay that takes into account the upstream history of plateletagonist interactions.…”
Section: A Platelet Activation and Adhesionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the low blood compatibility of the PDMS surface, a blocking agent (e.g., BSA) has generally been used to coat the PDMS and inhibit cell adsorption. 17,18,30 Accordingly, we next examined the extent of platelet adhesion to native PDMS surfaces, BSA-coated PDMS surfaces, and nanosheet-coated PDMS surfaces in order to validate the applicability of modified PDMS devices for hematological use. Various PDMS plates immersed in PRP were incubated for different hours before the observation.…”
Section: A Characterization Of the Modified Surfacesmentioning
confidence: 99%